(untitled) (American Journal of Islam and Society, 2009)
This paper assesses the ongoing dialogue and student exchange between the Mennonite Central Committee (MCC) and one of the most violent institutions in Iran, the Imam Khomeini Education and Research Institute (IKERI). I will use this relationship between theMCC and IKERI to examine the broader question of interreligious transnational dialogue and peacemaking. After a brief background of this somewhat “secretive” dialogue/ student exchange, I will evaluate its effects. Of particular interest will be the following questions: How do we responsibly shape Muslim–non-Muslim dialogue for peace and understanding in a global context that is inevitably shaped by an imbalance of power and representation? How are the acts of resistance undertaken by the disenfranchised local/diasporic Iranian communities and the sustained systematic violence against them impacted by a peaceful faith community such as the Mennonites? How does the absolutization of “dialogue” coupled with self-proclaimed theological mandates effectively strip away the archives of violence from living memories and histories?What can examining the decade-long dialogue between the MCC and IKERI reveal about the mechanisms of perpetuation and dissimulation of imperial domination and control? How can transnational interreligious interventions be the nexus for infusing sensitivity and expecting accountability? I argue that a fetishization of dialogue and a commodification of peacemaking took place between the MCC and IKERI, resulting in the patronage of the sign systems of existing normative ideologies of violence ...